A comparative study of predation rhythms on cladocerans by juvenile invasive crayfish and native shrimp - Zhang, Hui; Liu, Ying; Gao, Jian; Liao, Mingjun; Wang, Heyun; Ji, Yachan; Jiao, Yiying; Wan, Liang; Zhao, Xiaoyao; Jeppesen, Erik; Chen, Feizhou (Frontiers in Ecology and Evolution, 2026)
The red swamp crayfish Procambarus clarkii is one of the most widely distributed invasive species in the world. Effects of juvenile crayfish (< 5 cm in body length) in lake ecosystems remain largely unknown, despite that they have a great potential of preying upon zooplankton. The shrimp Exopalaemon modestus is one of the most abundant native shrimps in China and also predate on zooplankton. The predation rhythm of juvenile crayfish on zooplankton and how it differs from native shrimps remain to be studied. We elucidated the predation rhythms of juvenile and sub-adult crayfish and shrimps on Simocephalus mixtus, a common Cladocera in the littoral region of freshwater lakes. Predation rates during the day or at night were measured for juvenile crayfish (~3.75 cm in body length), sub-adult crayfish (~6.68 cm) and juvenile shrimp (~3.88 cm) at different zooplankton densities (18, 54, 108 ind./L representing low, medium and high natural densities, respectively). The results showed that (1) juvenile crayfish predated slightly more at night than during the day, and with significantly higher predation rates than sub-adult crayfish; (2) Juvenile shrimp predated significantly more at night than during the day, as predation was almost absent during the day; (3) Juvenile shrimp had slightly higher night-time predation rates than juvenile crayfish, however, their daytime predation rates were significantly lower at medium and high zooplankton densities. Juvenile crayfish fed for a longer period than shrimp of similar length, exhibiting higher feeding capacity on zooplankton which supports the inherent superiority hypothesis that invasive species possess advantages over native species in feeding capacity. Our study provides information about the predation rhythms on Cladocera of early stages of crayfish and of shrimp, that may help in explaining, in part, the invasion success of red swamp crayfish.